Cerebrospinal fluid findings in aquaporin-4 antibody positive neuromyelitis optica: Results from 211 lumbar punctures - Jarius, Sven; Paul, F.; Franciotta, D.; Ruprecht, K.; Ringelstein, M.; Bergamaschi, R.; Rommer, P.; Kleiter, I.; Stich, O.; Reuss, R.; Rauer, S.; Zettl, U. K.; et al. (Journal of the neurological sciences, 2011)
Background - Neuromyelitis optica (NMO, Devic disease) is a severely disabling autoimmune disorder of the CNS, which was considered a subtype of multiple sclerosis (MS) for many decades. Recently, however, highly specific serum autoantibodies (termed NMO-IgG or AQP4-Ab) have been discovered in a subset (60-80%) of patients with NMO. These antibodies were subsequently shown to be directly involved in the pathogenesis of the condition. AQP4-Ab positive NMO is now considered an immunopathogenetically distinct disease in its own right. However, to date little is known about the cerebrospinal fluid (CSF) in AQP4-Ab positive NMO. - Objective - To describe systematically the CSF profile of AQP4-Ab positive patients with NMO or its formes frustes, longitudinally extensive myelitis and optic neuritis. - Material and methods - Cytological and protein biochemical results from 211 lumbar punctures in 89 AQP4-Ab positive patients of mostly Caucasian origin with neuromyelitis optica spectrum disorders (NMOSD) were analysed retrospectively. - Results - CSF-restricted oligoclonal IgG bands, a hallmark of MS, were absent in most patients. If present, intrathecal IgG (and, more rarely, IgM) synthesis was low, transient, and, importantly, restricted to acute relapses. CSF pleocytosis was present in around 50% of samples, was mainly mild (median, 19cells/μl; range 6-380), and frequently included neutrophils, eosinophils, activated lymphocytes, and/or plasma cells. Albumin CSF/serum ratios, total protein and CSF L-lactate levels correlated significantly with disease activity as well as with the length of the spinal cord lesions in patients with acute myelitis. CSF findings differed significantly between patients with acute myelitis and patients with acute optic neuritis at the time of LP. Pleocytosis and blood CSF barrier dysfunction were also present during remission in some patients, possibly indicating sustained subclinical disease activity. - Conclusion - AQP4-Ab positive NMOSD is characterized by CSF features that are distinct from those in MS. Our findings are important for the differential diagnosis of MS and NMOSD and add to our understanding of the immunopathogenesis of this devastating condition.
Gesehen am 04.07.2022